Why a labour market boom does not necessarily bring down inequality: putting together Germany's inequality puzzle - Martin Biewen; Miriam Sturm (Fiscal Studies, 2022)
After an economically tough start to the new millennium, Germany experienced an unprecedented employment boom after 2005, only stopped by the COVID-19 pandemic. Persistently high levels of inequality despite a booming labour market and drastically falling unemployment rates constituted a puzzle, suggesting either that the German job miracle mainly benefitted individuals in the mid- or high-income range or that other developments offset the effects of the drastically improved labour market conditions. The present paper solves this puzzle by breaking down the observed changes in the distribution of disposable incomes between 2005–06 and 2015–16 into the contributions of eight different factors, one of them being the employment boom. Our results suggest that, while the latter did have an equalising impact, it was partially offset by the disequalising impact of other factors, and substantially dampened by the transfer system. Our results point to a strong role of the German transfer system as a distributional stabiliser implying that, if the COVID-19 shock were to persistently reverse all the employment gains that occurred during the boom, this would only have a moderately disequalising effect on the distribution of net~incomes.
Keywords: 330; employment; income distribution; labour market reform; social insurance